Chlorin e6 combined with albumin nanoparticles as a potential composite photosensitizer for photodynamic therapy of tumors - Shton, I.O.; Sarnatskaya, V.V.; Prokopenko, I.V.; Gamaleia, N.F. (Experimental Oncology, 2015)
Aim: To synthesize and to study for photodynamic activity a composite photosensitizer consisting of chlorin e6 and human serum albumin nanoparticles (HSA NPs). Materials and Methods: Starting from sorption-purified HSA, the albumin nanoparticles with a different degree of lysine residues cross-linking (10; 20; 40, and 100%) were obtained by the coacervation method. The HSA NPs were used for synthesis of nanocomposites with chlorin e6 and fluorescein isothiocyanate (FITC)-labled preparations. Malignant lymphocytes of the MT-4 (human T-cell leukemia) line and normal lymphocytes of healthy donors served as cell targets. For photodynamic treatment, a semiconductor laser was exploited as a light source, and cell viability was assessed by MTT or trypan blue dye exclusion tests. For cell imaging and HSA NPs visualization, the fluorescence microscopy and transmission electron microscopy were applied, respectively. C57Bl/6 mice were used in animal experiments. Results: The absorption and fluorescence spectra of chlorin e6-HSA NPs composites were characterized, and by the electron microscopy investigation the size of NPs (nanospheres) was estimated: 100–120 nm. FITC-labled albumin preparations allowed to establish that HSA NPs have much higher exposition and concentration dependent affinity to malignant cell surface than initial HSA. In experiments with MT-4 cells on PDT activity of chlorin e6-HSA NPs, the nanocomposite effectiveness elevated along with increasing percentage of cross-linked aminoacid residues, and for the nanocomposite with 100% of albumin cross-linking it exceeded the activity of free chlorin e6. In contrast to malignant cells, the complexation of chlorin e6 with HSA NPs decreased its photodynamic effect on normal human lymphocytes. Intravenous introduction of the chlorin e6-HSA NPs composite to mice showed prolonged circulation of the nanocomposite in blood in comparison with free PS. Conclusion: Promising results obtained with chlorin e6-HSA NPs composites warrant conduction of full-fledged PDT studies in vivo using the nanocomposites as photosensitizers. Key Words: human serum albumin, nanoparticles, photodynamic therapy, chlorin e6, cell line MT-4, C57Bl/6 mice.